Beyond Risk Transfer: Rethinking Dynamic Capabilities as the Foundation of Innovation in General Insurance Compa-nies - Pristiwanto Bani; Ratih Anggoro Wilis (Brilliant International Journal Of Management And Tourism, 2025)
General insurers are currently facing increasingly complex pressures as a result of accelerating digital disruption, rising customer expectations, and global risk dynamics. Amid these conditions, the traditional approach, which focuses on the primary function of risk transfer, is no longer considered sufficient to ensure long-term sustainability and competitiveness. This article aims to review the concept of dynamic capabilities as a strategic foundation in driving innovation in general insurance companies. Using the Narrative Literature Review (NLR) method, this study identifies three main dimensions of dynamic capabilities: sensing, seizing, and transforming, which play a crucial role in enhancing organizational responsiveness to market changes, technological opportunities, and external uncertainties. The results of the study show that insurance companies that can develop and integrate dynamic capabilities sustainably tend to be more adaptive and innovative in creating products, business models, and service strategies that meet future needs. The implementation of dynamic capabilities not only strengthens the company's competitiveness but also shifts the paradigm from just risk transfer to value co-creation. This research makes a theoretical contribution by developing a new conceptual framework that links dynamic capabilities with innovation in the general insurance sector, offering practical implications for the development of organizational transformation strategies. These findings also open up further research space to empirically examine the relationship between the dynamic capabilities, innovation, and performance of general insurers in an ever-changing industry context.